2021
DOI: 10.1101/2021.03.16.21253736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurological manifestations of patients with mild-to-moderate COVID-19 attending a public hospital in Lima, Peru

Abstract: Objective To determine the prevalence and characteristics of the most common neurological manifestations in Peruvian patients with mild-to-moderate COVID-19. Methods We conducted a single-center prospective, cross-sectional study at an isolation center functioning as a public acute-care hospital during the COVID-19 pandemic in Lima, the capital city of Peru. This was a convenience sample of patients with acute COVID-19 infection and mild-to-moderate respiratory symptoms who presented for hospital admission be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The COVID-19 pandemic increased rates of migraine more directly as well. In the previously mentioned cross-sectional study that investigated neurological symptoms in mild-to-moderate COVID-19 patients in Peru, headache was the most commonly reported symptom with a response rate of 72% (52). Compared to other studies with similar investigations in different countries, Peruvian patients recorded some of the highest rates of headache (52).…”
Section: Migraine Headachementioning
confidence: 82%
See 2 more Smart Citations
“…The COVID-19 pandemic increased rates of migraine more directly as well. In the previously mentioned cross-sectional study that investigated neurological symptoms in mild-to-moderate COVID-19 patients in Peru, headache was the most commonly reported symptom with a response rate of 72% (52). Compared to other studies with similar investigations in different countries, Peruvian patients recorded some of the highest rates of headache (52).…”
Section: Migraine Headachementioning
confidence: 82%
“…In addition to increasing the overall burden of disease, the COVID-19 pandemic has worsened the already growing burden of neurological diseases harming Peru. A recent cross-sectional study of Peruvian patients with mild-to-moderate COVID-19 found that 83% of patients reported at least one neurological symptom (52). Other studies found that stroke caused by COVID-19 infection led to remarkably high rates of mortality among Peruvian patients hospitalized with the disease (53,54).…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation